Teologi Intergratif: Model Refleksi Teologis untuk Menjembatani Ortodoksi dan Kontekstualitas dalam Teologi Kontemporer - Tambunan, Fernando (Sekolah Tinggi Teologi Sola Gratia Medan, 2025)
Abstract. This study aims to formulate the model of Intergrative Theology as a new paradigm in theological reflection, seeking to bridge the tension between orthodoxy (that which is held to be true) and contextuality (that which is relevant) in contemporary theology. This effort is motivated by the polarization between overly abstract classical systematic theology and contextual theology that is often deemed too readily adaptable. Conceptually,